Immunomodulation in the Treatment of Refractory Catastrophic Antiphospholipid Syndrome - Karthik Nath; Andrew McCann (Case Reports in Hematology)
Catastrophic antiphospholipid syndrome is a rare condition with high morbidity and mortality. We present a refractory case of catastrophic antiphospholipid syndrome with a view to highlight the importance of early identification and aggressive treatment of this condition. A 36-year-old female presented with clinical manifestations of multiorgan vascular occlusion with a known history of primary antiphospholipid syndrome. The presentation was on a background of a recent change of her long-term anticoagulation from warfarin to therapeutic low-molecular-weight heparin. Given that multiorgan involvement with 3 organ systems occurred nearly simultaneously, a diagnosis of probable catastrophic antiphospholipid syndrome was made. Prompt therapeutic anticoagulation, antiplatelet, and glucocorticoid therapy was commenced. Despite this, the patient continued to demonstrate clinical features concerning for ongoing small vessel occlusion necessitating aggressive immunomodulatory therapy in the form of intravenous immunoglobulin, plasma exchange, and rituximab.